Agricultural Productivity Growth and Poverty Reduction: Evidence from Thailand. (20th November 2020) - Warr, Peter; Suphannachart, Waleerat
Abstract: Raising agricultural productivity in developing countries is often said to reduce poverty more than comparable growth arising from other sectors. This claim has frequently been based on casual theorising, rather than empirical evidence. Productivity growth generates additional income and must benefit someone, though not necessarily the poor. It is conceivable that most, or even all of the benefits might go to others. Using region‐level data from Thailand, we study the relationship between agricultural productivity growth and rural poverty incidence. The dependent variable for our regression analysis is the annual rate of change in rural poverty incidence at the regional level between the years for which poverty data are available. Agricultural productivity is measured as the annual rate of change in regional total agricultural productivity, covering the same time intervals as the poverty observations, but lagged one calendar year. Other control variables include regional non‐agricultural incomes and the real price of food. The estimated coefficient on the change in agricultural productivity is negative and highly significant, implying that agricultural productivity growth does reduce rural poverty, holding other variables constant, though not more so than non‐agricultural sources of income growth. The poverty‐reducing contribution of recent agricultural productivity growth has been small. The poverty‐reducing effects of long‐term drivers of agricultural productivity growth are also analysed, using simulations based on the estimated model.